Investigating biases in the measurement of apparent alveolar septal wall thickness with hyperpolarized 129Xe MRI. Issue 6 (18th June 2020) - Ruppert, Kai; Amzajerdian, Faraz; Xin, Yi; Hamedani, Hooman; Loza, Luis; Achekzai, Tahmina; Duncan, Ian F.; Profka, Harrilla; Qian, Yiwen; Pourfathi, Mehrdad; Kadlecek, Stephen; Rizi, Rahim R.
Abstract : Purpose: To investigate biases in the measurement of apparent alveolar septal wall thickness (SWT) with hyperpolarized xenon‐129 (HXe) as a function of acquisition parameters. Methods: The HXe MRI scans with simultaneous gas‐phase and dissolved‐phase excitation were performed using 1‐dimensional projection scans in mechanically ventilated rabbits. The dissolved‐phase magnetization was periodically saturated, and the dissolved‐phase xenon uptake dynamics were measured at end inspiration and end expiration with temporal resolutions up to 10 ms using a Look‐Locker‐type acquisition. The apparent alveolar septal wall thickness was extracted by fitting the signal to a theoretical model, and the findings were compared with those from the more commonly use chemical shift saturation recovery MRI spectroscopy technique with several different delay time arrangements. Results: It was found that repeated application of RF saturation pulses in chemical shift saturation recovery acquisitions caused exchange‐dependent gas‐phase saturation that heavily biased the derived SWT value. When this bias was reduced by our proposed method, the SWT dependence on lung inflation disappeared due to an inherent insensitivity of HXe dissolved‐phase MRI to thin alveolar structures with very short T 2 ∗ . Furthermore, perfusion‐based macroscopic gas transport processes were demonstrated to cause increasing apparent SWTs with TE (2.5 μm/ms at end expiration) and a lung periphery‐to‐center SWT gradient. Conclusion: The apparent SWT measured with HXe MRI was found to be heavily dependent on the acquisition parameters. A method is proposed that can minimize this measurement bias, add limited spatial resolution, and reduce measurement time to a degree that free‐breathing studies are feasible.